2023
DOI: 10.1039/d2bm02109a
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid nanoparticles with cell membrane and dexamethasone-conjugated polymer for gene delivery into the lungs as therapy for acute lung injury

Abstract: Gene therapy has been suggested as a new treatment for acute lung injury (ALI), which is a severe inflammatory disease. Previously, amphiphilic polymeric carriers such as dexamethasone-conjugated polyethylenimine (PEI) (DP)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Zhuang et al prepared a delivery system coated with LA-4 lung epithelial cell membrane (CM) that significantly improved the delivery efficiency of pDNA to the lungs, surpassing the anti-inflammatory effect of the delivery system without cell membrane encapsulation. 125…”
Section: Strategies To Improve Gene Transfection Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Zhuang et al prepared a delivery system coated with LA-4 lung epithelial cell membrane (CM) that significantly improved the delivery efficiency of pDNA to the lungs, surpassing the anti-inflammatory effect of the delivery system without cell membrane encapsulation. 125…”
Section: Strategies To Improve Gene Transfection Efficiencymentioning
confidence: 99%
“…Zhuang et al developed a hybrid nanoparticle combining dexamethasone-coupled polyethyleneimine (DP) with cell membranes (CM) from LA-4 lung epithelial cells. 125 The aim was to improve the delivery efficiency of pDNA to the lungs. The CM in the hybrid nanoparticles interacted with the plasma membrane of the target cells, promoting cellular uptake of pDNA.…”
Section: Biological Applicationmentioning
confidence: 99%
“…The use of cell membranes or microvesicles to encapsulate nanoparticles reduces their recognition and removal by the immune system, as these membranes are derived from the body’s own cells and are naturally biocompatible. Cell membranes or microvesicles may contain specific proteins or receptors that can bind to specific markers in lung cells, thus improving lung targeting [ 156 ]. Camouflaged nanoparticles can cross biological barriers, such as the blood‒air barrier, more efficiently, thereby increasing the efficiency of the drug in reaching the lungs.…”
Section: Types Of Nanomaterials Targeted To Treat Alimentioning
confidence: 99%
“…9−11 Besides, the LPEImediated intravenous gene delivery affords the highest level of transgene expression selectively in the lung tissue. 12,13 This targeted expression in the lung implies massive potential of the LPEI and its analogues for nonviral gene therapy against lung cancer. For example, Rodrigo-Garzoń et al showed intravenous IL-12 gene transfer by the LPEI for the gene therapy against metastatic lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative to those BPEIs, 25 kDa linear PEI (LPEI) holds much lower in vitro and in vivo toxicity as compared to the BPEI, thus enabling solid tumor gene therapy by intravenous or intratumoral injection. Besides, the LPEI-mediated intravenous gene delivery affords the highest level of transgene expression selectively in the lung tissue. , This targeted expression in the lung implies massive potential of the LPEI and its analogues for nonviral gene therapy against lung cancer. For example, Rodrigo-Garzón et al showed intravenous IL-12 gene transfer by the LPEI for the gene therapy against metastatic lung cancer .…”
Section: Introductionmentioning
confidence: 99%